O acesso glissoniano intra-hepático nas ressecções do fígado - Martins,Antonio Cavalcanti de A. (2008)
The intra-hepatic glissonian approach has been considered an advance in the modern hepatic surgery by allowing a safe resection, with minor bleeding and maximum preservation of hepatic tissue. This paper explores the history, the anatomy, the techniques and how to perform and understand the intra-hepatic glissonian approaches.